Measurement and calibration requirements for quality assurance to ISO 9000 - Morris, Alan S. 1948- (Wiley series in quality and reliability engineering, 1997)
This uniquely integrated approach to quality management focuses on the measurement and calibration requirements that are key to the achievement of ISO 9000. The cross-disciplinary approach makes this well-structured text an invaluable asset both to engineers concerned with the development, implementation and maintenance of quality systems and to managers wishing to gain an insight into quality assurance issues.